Explorations in the anthropology of religion
VI, 303 p. 6 illus.
Keywords: This Festschrift is dedicated to Prof. Dr. J. van Baal on the occasion of his retirement from the chair of cultural anthropology at the University of Utrecht. The essays presented here are written by fellow scholars in recognition of his outstanding contributions to the field of anthropology. In order to arrange the papers araund a theme that has never ceased to fascinate van Baal, we have asked the contributors to concentrate on a rel igious subject. Within this broad area no specific topics have been solicit ed, and the authors-- mainly fellow anthropologists and students of relig ion-- have been able to pursue their own personal interests in the articles. Nevertheless, when the papers were collected, we found it possible to group them under three headings, each of which represents a facet of ·1an Baal's enduring interests. Of course, some overlap is inevitable, as it is in any categorisation of heterogeneaus items. The topics of the three sections by no means represent an exhaustive inventory of all fields van Baal has successfully explored. The focus on religion necessarily leaves out many problems van Baal has actively occ- ied hirnself with during his many-sided career. Thus the academic stance of the Festschrift in no way pays tribute to his prolonged concern with admi.